2002
DOI: 10.1159/000066132
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Relationship between Antisocial Personality Disorder and Alcohol Dependence

Abstract: Personality disorders, and particularly antisocial personality disorder (ASPD), frequently co-occur with alcohol dependence. ASPD is considered to be an important cofactor in the pathogenesis and clinical course of alcohol dependence. The chronological relationship between the onset of symptoms of ASPD and alcohol-dependence characteristics has not yet been studied in great detail and the role of ASPD in classification schemes of alcohol dependence as suggested by Cloninger and Schuckit has yet to be determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
3
9
0
1
Order By: Relevance
“…Finally, our results agree with prior studies indicating that sensation‐seeking and ASPD are strong risk factors for heavy alcohol use . The interactions we discovered suggest that one mechanism by which these factors lead to heavy alcohol use is by making people less sensitive to otherwise‐protective factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, our results agree with prior studies indicating that sensation‐seeking and ASPD are strong risk factors for heavy alcohol use . The interactions we discovered suggest that one mechanism by which these factors lead to heavy alcohol use is by making people less sensitive to otherwise‐protective factors.…”
Section: Discussionsupporting
confidence: 91%
“…ASPD is characterized by a pervasive pattern of disregard for, and violation of, the rights of others and social norms that begins in early childhood or adolescence and continues into adulthood . It is associated strongly with heavy alcohol and drug use . Finally, ADHD is characterized by symptoms of inattention and/or hyperactivity–impulsivity that start in childhood or adolescence and can continue into adulthood .…”
Section: Introductionmentioning
confidence: 99%
“…The same pattern was reported in university students (Sher, Bartholow, & Wood, 2000). Third, a recent study found that the onset of ASPD characteristics precedes that of alcohol dependence by some 4 years (Bahlman, Preuss, & Soyka, 2002). The relationship between behavioural disinhibition and early onset addictive behaviours is probably mediated through deficient socialisation, school failure, and affiliation with deviant peers (Sher & Trull;Tarter & Vanyukov, 1994;Wills, Windle, & Cleary, 1998).…”
Section: Primary Personality Disorder Modelsupporting
confidence: 65%
“…Researchers concluded that patients classifi ed as type II are more predisposed to noncompliance with program rules due to the unstable personality traits that commonly characterize them (Pombo et al 2010). However, doubts remain whether these clinical unstabilized factors can be better explained by a polydrug lifestyle or antisocial personality traits, even when the events are independent of alcohol or drug intoxication (Schuckit and Irwin 1989;Hauser and Rybakowski 1997;John et al 2001;Bahlmann et al 2002). Type IV also presented lower healthcare resource use and more relapses aft er planned outpatient medical detoxifi cation when compared with the other LAT subtypes.…”
Section: Discussionmentioning
confidence: 99%